The Nature and Influence of Pharmaceutical Industry Involvement in Asthma Trials - Kenneth Bond; Carol Spooner; Lisa Tjosvold; Catherine Lemière; Brian H Rowe (Canadian Respiratory Journal)
BACKGROUND: Pharmaceutical industry-sponsored research has been shown to be biased toward reporting positive results. Frequent industry participation in trials assessing the efficacy of inhaled corticosteroid (ICS) and long-acting beta2-agonist (LABA) combination treatment makes assessing industry influence difficult and warrants an assessment of specific potential publication bias in this area.